2021
DOI: 10.1126/sciadv.abf2725
|View full text |Cite
|
Sign up to set email alerts
|

Reversible 3D-2D structural phase transition and giant electronic modulation in nonequilibrium alloy semiconductor, lead-tin-selenide

Abstract: Material properties depend largely on the dimensionality of the crystal structures and the associated electronic structures. If the crystal-structure dimensionality can be switched reversibly in the same material, then a drastic property change may be controllable. Here, we propose a design route for a direct three-dimensional (3D) to 2D structural phase transition, demonstrating an example in (Pb1−xSnx)Se alloy system, where Pb2+ and Sn2+ have similar ns2 pseudo-closed shell configurations, but the former sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…The large decrease of μ in 2D (Pb 1−x Sn x ) Se from that of 3D one originates from the electronic structure change from a gapless state to a semiconducting state as reported in Ref. [27]. The bandgap change was confirmed by diffuse reflectance measurement of (Pb 1−x Sn x )Se bulks shown in Section 3 of Supporting Information.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The large decrease of μ in 2D (Pb 1−x Sn x ) Se from that of 3D one originates from the electronic structure change from a gapless state to a semiconducting state as reported in Ref. [27]. The bandgap change was confirmed by diffuse reflectance measurement of (Pb 1−x Sn x )Se bulks shown in Section 3 of Supporting Information.…”
Section: Resultssupporting
confidence: 68%
“…[24,25] To overcome the issue, we previously developed a nonequilibrium thin-film growth technique combining reactive solidphase epitaxy and thermal quenching from 873 K to room temperature (RT). [26,27] The rapid quenching is effective to freeze the larger x 3D and the smaller x 2D (Pb 1−x Sn x )Se phases that are stable only at high T (as shown by the blue arrows in Figure 1b). However, even by this quenching method from 873 K, the 3D and the 2D (Pb 1−x Sn x )Se films were formed only in rather narrow ranges x ≤ 0.5 and x ≥ 0.8, respectively, where mixed phase was formed between them, presumably because of the insufficient heating temperature restricted by severe evaporation of the thin film.…”
Section: Resultsmentioning
confidence: 99%
“…However, we consider that the solubility limit can be increased at high temperatures because the entropy term has a greater contribution with increasing temperatures. We previously reported that the non-equilibrium synthesis by high-temperature solid-state reaction and subsequent rapid thermal quenching could expand the solubility limit of Pb in 2D-layered (Sn 1– x Pb x )Se bulk polycrystals for x = 0.2–0.5, ,, that of Sn in 3D cubic (Sn 1– x Pb x )Se bulks for x = 0.6–0.5, and that of Te in 2D-layered Sn­(Se 1– x Te x ) bulks for x = 0.2–0.4 . Additionally, non-equilibrium vapor phase thin film deposition stabilized the 3D cubic (Sn 1– x Ca x )Se with x = 0.4–0.8, which cannot be obtained through equilibrium synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…However, Pb 2+ ion substitution largely reduces the bandgap and produces a gap-less Dirac-like state in cubic (Sn 1– x Pb x )­Se because the contribution of the deep Pb 6p orbital shifts down the conduction band minimum (CBM). The large Pb 2+ ion enhances the hybridization of Se 4p orbitals with Pb 6s and 5p orbitals, resulting in a shift up of the valence band maximum (VBM) . Such a very narrow bandgap in cubic (Sn 1– x Pb x )Se inevitably provides a high carrier concentration of ∼10 19 cm –3 , which is not suitable for semiconductor device applications because high donor/acceptor densities reduce carrier lifetime and energy conversion efficiency in solar cells and high free carrier densities can not be depleted by gate bias and inhibit to turn off field effect transistors.…”
Section: Introductionmentioning
confidence: 99%
“…The large Pb 2+ ion enhances the hybridization of Se 4p orbitals with Pb 6s and 5p orbitals, resulting in a shift up of the valence band maximum (VBM). 19 Such a very narrow bandgap in cubic (Sn 1−x Pb x )Se inevitably provides a high carrier concentration of ∼10 19 cm −3 , which is not suitable for semiconductor device applications because high donor/acceptor densities reduce carrier lifetime and energy conversion efficiency in solar cells and high free carrier densities can not be depleted by gate bias and inhibit to turn off field effect transistors. In addition, direct film deposition in vacuum at a high temperature is difficult because of the high vapor pressure of Pb.…”
Section: Introductionmentioning
confidence: 99%